2019
DOI: 10.1002/ceat.201800696
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Cobalt Salts for Recovery in Leachates

Abstract: Metals such as cobalt are particularly strategic since they are present in many high-added-value products. Besides, at the rate of current consumption, specifically of cobalt, the manufacturers are facing risks of shortage for their supply. So, research on these metals' recovery from industrial or urban waste is highly important for the future. Current work focuses on cobalt recovery from Li-ion batteries by precipitation. Literature was evaluated on the various anions allowing to precipitate Co(II), in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…A literature review, as well as speciation simulations, showed that 99.8 % of the cobalt could be recovered by hydroxide precipitation [10]. Afterward, several simulations were performed with Visual Minteq 3.0.…”
Section: How To Recover Cobalt From Battery Leachatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review, as well as speciation simulations, showed that 99.8 % of the cobalt could be recovered by hydroxide precipitation [10]. Afterward, several simulations were performed with Visual Minteq 3.0.…”
Section: How To Recover Cobalt From Battery Leachatesmentioning
confidence: 99%
“…According to the United States Geological Survey, the DRC provided nearly 65 % of the world's cobalt supply in 2018 and could continue to increase its output [9]. In addition to this, the DRC has plunged into a political slump and the country's macroeconomy is fragile [10]. Moreover, artisanal mining and child labor in Congolese mines are the cause of dramatic humanitarian situations [11].…”
Section: Introduction 1cobalt Criticality Evaluationmentioning
confidence: 99%
“…The experiments showed that for a molar ratio lower than 2, cobalt (II) hydroxide of type α-Co(OH) 2 is formed. Indeed, supersaturation is not sufficient for the rapid polymorphic transition from α-Co(OH) 2 to β-Co(OH) 2 [40]. Studies have shown that for a molar ratio n OH − /n Co 2+ between 1 and 1.8, the polymorph α-Co(OH) 2 remained stable, its conversion to the β-Co(OH) 2 form is very long.…”
Section: Precipitation Of Co(oh) 2 In Continuous Reactor At 25 • Cmentioning
confidence: 99%
“…Second, hydrometallurgical processes for the recovery of metals from the alloys employ leaching step by inorganic and organic acidic solution such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), nitric acid (HNO 3 ), citric acid, oxalic acid and tartaric acid 16‐22 . The separation of metal ions from the leaching solutions is performed by solvent extraction, ion exchange, membrane and precipitation 23‐27 . However, the separation of metal ions in the presence of various elements such as Co(II), Ni(II), Cu(II), Mn(II) and Fe(III) from their leaching solutions is rather complicated, and the separation methods depend significantly on both the concentration of metal ions and the speciation of metal ions in the leaching solution.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] The separation of metal ions from the leaching solutions is performed by solvent extraction, ion exchange, membrane and precipitation. [23][24][25][26][27] However, the separation of metal ions in the presence of various elements such as Co(II), Ni(II), Cu(II), Mn(II) and Fe(III) from their leaching solutions is rather complicated, and the separation methods depend significantly on both the concentration of metal ions and the speciation of metal ions in the leaching solution. Meanwhile, few works have reported the recovery of Li from the slag and dust.…”
Section: Introductionmentioning
confidence: 99%